"Electromagnetic barrier" assisted dynamic spectrum access in satellite internet communication confrontation. Issue 18 (27th July 2022) - Yan, Peijie; Chu, Feihuang; Jia, Luliang; Qi, Nan
Abstract: In this paper, the dynamic spectrum access is investigated in satellite internet. Firstly, to describe the confrontation characteristics of the electromagnetic environment, two opposing teams denoted as the blue team (BT) and red team (RT), are designed. In addition, an "electromagnetic barrier" jamming strategy is proposed to achieve the effect of promoting approach defence with the attack. Precisely, the "electromagnetic barrier" can significantly weaken the communication ability of enemies (i.e. RT) while protecting the (i.e. BT) communication quality. Secondly, internal interference, external interference and malicious jamming of BT and RT are considered, and expected weighted aggregate interference and jamming (EWAIJ) are introduced to integrate these interference. Moreover, minimising interference is taken as the optimisation goal. Thirdly, Game theory is introduced to describe the combinatorial optimisation problem. The process of each team finding the optimal spectrum access strategy is proved to be an exact potential energy game. These two sub‐games together constitute the Stackelberg game framework. Finally, a distributed hierarchical confrontation channel selection algorithm (DHCCSA) is proposed to find the Stackelberg equilibrium solution. The simulation results show that the proposed algorithm can converge to a better effect compared with other algorithms. In addition, with the assistance of the "electromagnetic barrier, " BT is more robust than RT in terms of convergence rate, total utility, and total network throughput.